Primary Prevention Strategy for Non-Communicable Diseases (NCDs) and Their Risk Factors: The Role of Intestinal Microbiota - Itzel Ivonn López-Tenorio; Óscar Rodrigo Aguilar-Villegas; Yoshua Espinoza-Palacios; Lorena Segura-Real; Berenice Peña-Aparicio; Amedeo Amedei; María Magdalena Aguirre-García (Biomedicines)
Non-communicable diseases (NCDs) are the leading cause of morbidity and mortality worldwide. These conditions have numerous health consequences and significantly impact patients’ lifestyles. Effective long-term treatment is essential since NCDs are irreversible. Therefore, primary healthcare must be both exclusive and of the highest quality, ensuring comprehensive care. The primary goal should be to improve quality of life with a focus on patients, families, and communities, as most of these diseases can be prevented and controlled, although not cured. Several factors have been linked to individual health, including social, cultural, and economic aspects, lifestyle, and certain environmental factors, including work, that can have positive or negative effects. More of these variables may contribute to the onset of NCDs, which are defined by their chronic nature, propensity for prolongation, and generally slow rate of progression. Examples of NCDs include hypertension, type 2 diabetes (T2D), dyslipidemia, and fatty liver disease linked to metabolic dysfunction. The onset of these diseases has been associated with an imbalance in certain microbial niches, such as the gut, which hosts billions of microorganisms performing multiple metabolic functions, such as the production of metabolites like bile acids (BAs), short-chain fatty acids (SCFAs), and trimethylamine N-oxide (TMAO). Therefore, lifestyle changes and personal habits can significantly impact the gut microbiota (GM), potentially preventing chronic diseases associated with metabolism. NCDs are highly prevalent worldwide, prompting increased attention to strategies for modifying the intestinal microbiota (IM). Approaches such as probiotics, prebiotics, synbiotics, and fecal transplantation (FMT) have demonstrated improvements in the quality of life for individuals with these conditions. Additionally, lifestyle changes and the adoption of healthy habits can significantly impact IM and may help prevent chronic diseases related to metabolism. Therefore, the main aim of this review is to analyze and understand the importance of microbiota intervention in the prevention of non-communicable diseases. R3:A1